Congestion strategy of weekday peak-hour private vehicle usage in Singapore’s central business district (CBD) : a regression analysis - Boey, Carol Qian Liu (2016)
Traffic congestion in the city centre is a prevalent issue in many developed countries including Singapore, where detrimental effects to GDP include decreasing productivities due to time lost and business activity disruptions. This paper analyses how the congregation of business activities, or “Lure” factor of the Central Business District (CBD), contributes to the peak-hour CBD traffic congestion. Our results found that the “Lure” proxies used, namely, the formation of business entities in the finance and insurance sector and the rental value of office spaces, are significant in explaining the variations in the private cars and vehicles transactions counts into the CBD, especially during the morning peak-hour periods. Despite the effectiveness of congestion pricing as a urban traffic strategy, it might not be a sustainable solution in the long run as it is at best a stop-gap measure which does not address the root cause of CBD peak-hour congestion. Hence, our findings are in support of the government’s move to decentralise the current CBD so as to spread its congregation of business activities and reduce its employment density to other regional centres. Other viable options are to increase flexibility in working hours and work schedules.